Anaphylaxis after Moderna COVID-19 vaccine - Jeremy Mayfield; Sumedha Bandi; Latha Ganti; Jose Rubero (SAGE Publishing, 2021)
The authors of this article report on a case of a patient who presented to the emergency department (ED) in anaphylaxis after receiving the Moderna® COVID-19 vaccine. The patient was hypoxic, with diffuse wheezing bilaterally to auscultation, flush skin, swollen face, and the feeling of her throat closing. Anaphylaxis can have wide range of presentation, the key is recognizing the symptoms and treating early. The incidence of anaphylaxis from COVID-19 vaccine is not well documented to date.